Answer:
For a geometric sequence with recurrence of the form a(n)=ra(n-1) where r is constant, each term is r times the previous term. This implies that to get from the first term to the nth term, we need to multiply by n-1 factors of r.
Step-by-step explanation:
hii
you are looking so h*t and s**y..
Answer:
There is no picture
Step-by-step explanation:
Solution/Answer : 4
Solution: the first you do is multiply the last two parentheses to get -10xy
Now we are left with ( -2/5x)(-10xy)
Then we multiply that out into
(-2*-10)/5*x^2y = 20/5x^2y =
4x^2y
The coefficient in this case would be four. (In case you were confused about what a coefficient actually is, it’s the number you multiply a variable by)
Hopes this helps :)
3^x = 729
log(3^x) = log(729)
xlog(3) = log(729)
x = log(729)/log(3)
x = 6